Effects of Immune Activation during Early or Late Gestation on N-Methyl-d-Aspartate Receptor Measures in Adult Rat Offspring - Rahman, Tasnim; Zavitsanou, Katerina; Purves-Tyson, Tertia; Harms, Lauren R.; Meehan, Crystal; Schall, Ulrich; Todd, Juanita; Hodgson, Deborah M.; Michie, Patricia T.; Weickert, Cyndi Shannon (Frontiers in Psychiatry, 2017)
Background: Glutamatergic receptor [N-methyl-D-aspartate receptor (NMDAR)] alterations within cortex, hippocampus, and striatum, are linked to schizophrenia pathology. Maternal immune activation (MIA) is an environmental risk factor for the development of schizophrenia in offspring. In rodents, gestational timing of MIA may result in distinct behavioural outcomes in adulthood, but how timing of MIA may impact the nature and extent of NMDAR-related changes in brain is not known. We hypothesise that NMDR-related molecular changes in rat cortex, striatum and hippocampus are induced by MIA and are dependent on the timing of gestational inflammation and sex of the offspring. Methods: Wistar dams were treated with viral mimic, polyinosinic:polycytidylic acid (polyI:C), or vehicle on either gestational day (GD) 10 or 19. Fresh-frozen coronal brain sections were collected from offspring between postnatal day 63-91. Autoradiographic binding was used to infer levels of the NMDAR channel, and NR2A and NR2B subunits in cortex (cingulate, motor, auditory), hippocampus [dentate gyrus, cornu ammonis area (CA) 3, CA1], and striatum (dorsal striatum, nucleus accumbens core and shell). NR1 and NR2A mRNA levels were measured by in situ hybridisation in cortex, hippocampus, and striatum in male offspring only. Results: In the total sample, NMDAR channel binding was elevated in the cingulate cortex of polyI:C offspring. NR2A binding was elevated, while NR2B binding was unchanged, in all brain regions of polyI:C offspring overall. Male, but not female, polyI:C offspring exhibited increased NMDAR channel and NR2A binding in the striatum overall, and increased NR2A binding in the cortex overall. Male polyI:C offspring exhibited increased NR1 mRNA in the nucleus accumbens shell, and increased NR2A mRNA in cortex and subregions of the hippocampus. Conclusions: MIA may alter glutamatergic signalling in cortical and hippocampal regions via alterations in NMDAR indices, however this was independent of gestational timing. Male MIA offspring have exaggerated changes in NMDAR compared to females in both the cortex and striatum. The MIA-induced increase in NR2A may decrease brain plasticity and contribute to the exacerbated behavioural changes reported in males and indicate that the brains of male offspring are more susceptible to long-lasting changes in glutamate neurotransmission induced by developmental inflammation.